Gender identity and manifestations of love in marriage - Kamenov, Željka (Array, 2012)
Sociostructural theorists suggest that, due to differences in socialization, men and women are predisposed to express love differently. The current study builds on the assumptions of sociostructural theory and examines whether trait expressiveness, trait instrumentality, and gender-related attributes and attitudes—in addition to gender—predict the ways men and women report showing love (e.g., emotional openness, physical affection, domestic instrumentality, chivalry). We surveyed 302 married couples from Croatia and 456 married couples from Serbia who ranged in age from 20 to 82, and who came from both urban and rural backgrounds. Consistent with prior research, results indicated that women were more expressive, less instrumental, and held more egalitarian attitudes than men. Importantly, gender accounted for only a small amount of variance for these variables. We also examined the extent to which individuals’ trait expressiveness, trait instrumentality, and attitudes toward gender roles (versus gender) predicted their tendency to report showing love to one's partner in various ways. Slightly different patterns emerged among Croatian and Serbian spouses. Although trait expressiveness was tied to the different ways individuals report showing love across both cultures, trait instrumentality and gender attitudes surfaced as important predictors in the Serbian and Croatian samples, respectively. Additionally, results indicated that gender itself explained more variance in domestic instrumentality and chivalrous displays of love, whereas emotional openness and physical affection were better explained by gender-related attributes and attitudes.